Effects of Solo and Pair Programming Instructional Strategies on Students’ Academic Achievement in Visual-Basic.Net Computer Programming Language - Owolabi, J.; Adedayo, O.A.; Amao-Kehinde, A.O; Olayanju, T.A. (GSTF International journal on computing, 2014)
This study assesses the relative effectiveness of solo and pair programming instructional strategies on students’ academic achievement in the Visual-Basic.Net Computer Programming Language. Two research questions and three null hypotheses guided the study. The sample comprised 68 subjects distributed over the three treatment groups (27 solo programmers, 24 pair programmers, and 17 conventional programmers) from three hundred computer science students of the Federal College of Education (Technical), Akoka, Yaba, Lagos State, Nigeria. The Visual-Basic.Net Achievement Test (VAT) was used to collect data for both the pre- and post-tests. The VAT test was administered to all 68 subjects in the three groups, first as pre-test and after treatment as post-test. Mean and standard deviations were used to answer the two research questions while ANCOVA and multiple comparisons were used in testing the three null hypotheses. The results of the analyses indicate that: (i) the experimental groups performed better than the control group, (ii) the treatment appeared to be more effective among male students than their female counterparts, (iii) the main effects of treatment and gender as well as the interaction effects of treatment and gender were not statistically significant.